2014
DOI: 10.2466/06.15.pr0.114k27w8
|View full text |Cite
|
Sign up to set email alerts
|

Exertional Responses to Sprint Interval Training: A Comparison of 30-sec. and 60-sec. Conditions

Abstract: The purpose of this study was to assess the effect of sprint interval training on rating of perceived exertion. 20 healthy participants (11 men, 9 women; M age = 23 yr.) completed a maximal cycle ergometer test and two high-intensity interval training cycling sessions. Each session utilized the same work-to-rest ratio (1:1), work intensity (90% max), recovery intensity (10% work intensity), and session duration (16 min.). Trials differed on duration of the interval segment, with a 30-sec. trial and a 60-sec. t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
20
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 24 publications
5
20
0
2
Order By: Relevance
“…Overall, it is evident that more intense exercise elicits higher arousal and RPE and less positive affect than moderate exercise (18), yet whether this occurs in response to different intensities of interval training is unresolved. When interval training was matched for intensity yet duration differed, data (33) showed that a 60-second bout led to higher RPE (0-10 scale) than a 30-second bout. Price and Moss (42) demonstrated greater perceived exertion (6-20 scale) coincident with greater indices of metabolic perturbation (blood lactate, pH, etc.)…”
Section: Introductionmentioning
confidence: 93%
“…Overall, it is evident that more intense exercise elicits higher arousal and RPE and less positive affect than moderate exercise (18), yet whether this occurs in response to different intensities of interval training is unresolved. When interval training was matched for intensity yet duration differed, data (33) showed that a 60-second bout led to higher RPE (0-10 scale) than a 30-second bout. Price and Moss (42) demonstrated greater perceived exertion (6-20 scale) coincident with greater indices of metabolic perturbation (blood lactate, pH, etc.)…”
Section: Introductionmentioning
confidence: 93%
“…When considering the role of psychological perceptions (such as affect and enjoyment) in HIIT and SIT as types of PA, results to date have been equivocal (Oliveira et al 2013;Kilpatrick and Greeley 2014;Kilpatrick et al 2015b;Saanijoki et al 2015), though some reports demonstrate greater enjoyment of HIIT compared with MICT in overweight and healthy individuals (Bartlett et al 2011;Crisp et al 2012). Interestingly, direct comparison between SIT (8 × 30 s at 130% maximal work separated by 90 s of recovery, ϳ79% age-predicted maximal heart rate) and HIIT (8 × 60 s at 85% maximal work with 1 min of recovery, ϳ77% age-predicted maximal heart rate) in young active individuals found that the affective responses were similar despite greater blood lactate concentrations and perceived exertion during SIT (Wood et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the few studies on the psychological aspects of SIT have been limited in the constructs assessed (e.g., perceived exertion (Kilpatrick et al 2015b)). Another SIT study only assessed traditional (30 s) or longer sprint bouts (60 s) in young healthy participants (Kilpatrick and Greeley 2014), although the practicality is questionable considering traditional 30-s SIT is already highly demanding. Moreover, many SIT protocols have shown promising physiological results from very brief (8-15 s) sprint interval durations (Trapp et al 2008;Hazell et al 2010) and minimal (10-20 min/session) total time commitments (Metcalfe et al 2011;.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only 4HIIT increased VO 2 max after 6-week intervention, probably due to a longer tVO 2 max and improved estimated stroke volume. However, a shorter duration of the peak workload duration may lessen perceived exertion for individuals with a low aerobic fitness [14][15][16] and may easily be sustained and be performed with more repetitions, resulting in a similar tVO 2 max. 16 Matsuo et al 17,18 has proposed 3 × 3 min HIIT as a suitable protocol for Japanese as shown in his excellent review of HIIT studies among patients with obesity and metabolic syndrome.…”
Section: Hiit Protocolsmentioning
confidence: 99%